Some Fixed-Point Theorems on Generalized Cyclic Mappings in B-Metric-Like Spaces - Shengquan Weng; Quanxin Zhu (Complexity)
In this paper, it is concerned with the cyclic mapping in b-metric-like spaces. The definition of W-type cyclic mappings is proposed, and then, the existence-uniqueness of the fixed points of these cyclic mappings and the corresponding fixed point theorems are studied. In b-metric-like spaces, the promotion of the concept of cyclic mapping is an interesting topic; then, it is worthy to continue to this part of the promotion. On this basis, the concept of φ-type cyclic mapping is proposed in this article, and the existence-uniqueness of fixed-point problems and the corresponding fixed-point theorem are considered and studied. The results of this paper further generalize and extend some previous results.